Dynamic assessment of elicited imitation: A case analysis of an advanced L2 English speaker. (October 2014) - van Compernolle, Rémi A.; Zhang, Haomin (Stanley)
The focus of this paper is on the design, administration, and scoring of a dynamically administered elicited imitation test of L2 English morphology. Drawing on Vygotskian sociocultural psychology, particularly the concepts of zone of proximal development and dynamic assessment, we argue that support provided during the elicited imitation test both reveals and promotes the continued growth of emerging L2 capacities. Following a discussion of the theoretical and methodological background to the study, we present a single case analysis of one advanced L2 English speaker (L1 Korean). First, we present overall scores, which include three types: an "actual" score, based on first responses only; a "mediated" score, which is weighted to account for those abilities that become possible only with support; and a learning potential score, which may be used as a predictor of readiness to benefit from further instruction. Second, we illustrate how an item analysis can be useful in developing a detailed diagnostic profile of the learner that accounts for changes in the learner's need for, and responsiveness to, support over the course of the task. In concluding, we consider the implications of our approach to dynamically assessing elicited imitation tasks and directions for further research.